Carbon quantum dot/mixed crystal TiO2 composites via a hydrogenation process: an efficient photocatalyst for the hydrogen evolution reaction. Issue 99 (11th October 2016) - Tang, Yunqi; Hao, Rong; Fu, Yu; Jiang, Yong; Zhang, Xiangcheng; Pan, Qingjiang; Jiang, Baojiang
Abstract : High-performance photocatalyst including mixed crystal TiO2 /carbon quantum dots was obtained via a facile approach, which exhibited excellent property for hydrogen evolution under solar light. Abstract : The creation of stable and efficient photocatalysts that produce hydrogen from water under solar light is a burgeoning area of research. As a prospective candidate, TiO2 has been widely studied. Herein, we further designed and synthesized composites of mixed crystal TiO2 with high-performance carbon quantum dots (CQDs) via a facile approach. The CQDs were made by electrolyzing graphite rods and the mixed crystal TiO2 from titanium oxysulfate under a hydrothermal reaction, and then the resulting materials were heated to a high temperature under H2 . All the characterization proved that the CQDs had been successfully modified onto TiO2 with both anatase and brookite phases. The newly synthesized samples showed an excellent performance for hydrogen evolution using AM 1.5 light sources. The large hydrogen evolution yield was 280 μmol h −1, which was higher than that produced by pure TiO2 . It indicates that CQDs as electron storage could improve the separation of charges and inhibit the recombination of electron–hole pairs. Concurrently, the formation of heterostructures between the two phases of TiO2 would help electron–hole separation, which is another reason for the good performance of the photocatalyst.